Enhancing Law Student Learning - The Nurturing Teacher - Nikki Bromberger (Legal Education Review, 2010)
An ability to recognise and resolve ethical dilemmas was identified by the Australian Law Reform Commission as one of the ten fundamental lawyering skills. While the ‘Priestley 11’ list of areas of law required to qualify for legal practice includes ethics and professional responsibility, the commitment to ethics learning in Australian law schools has been far from uniform. The obligation imposed by the Priestley 11 is frequently discharged by a traditional teaching and learning approach involving lectures and/or tutorials and focusing on the content of the formal rules of professional responsibility. However, the effectiveness of such an approach may be open to question. Instead, a practical rather than a theoretical approach to the teaching of legal ethics is required. Effective final year student learning of ethics may be achieved by an approach which engages students, enabling them to appreciate the relevance of what they are learning to the real world and facilitating their transition from study to their working lives. Entry into Valhalla comprises a suite of modules featuring ‘machinima’ (computer generated imagery) created using the Second Life virtual environment to contextualise otherwise abstract concepts. It provides an engaging learning environment which enables students to obtain an appreciation of ethical responsibility in a real world context and facilitates understanding and problem-solving ability.